TECHNOLOGY AND QUALITY OF SOUCES BASED ON COMPOSITIONAL MIXTURES (Collection of research papers «PROGRESSIVE TECHNIQUE AND TECHNOLOGIES OF FOOD PRODUCTION ENTERPRISES, CATERING BUSINESS AND TRADE», 2025)
The article presents a technology for sauces with incorporating a compositional mixtures. Comprehensive research using organoleptic, physicochemical methods have proven the possibility and feasibility of using a composition of dietary supplements (dry demineralized whey, soy protein-fat supplement, gum arabic, pectin) to increase nutritional value and improve the quality of sauces.The developed mixture of dry whey and soy flour was added to the recipe of the sauces instead of flour. The classic sauce recipe was used as the control sample. New sauces with dry whey and compositional mixtures were prepared. Dry whey and composite mixtures are characterized by a high protein content, which has certain functional properties and play a major role in the process of structuring of sauce emulsion.The possibility and expediency of using the composition of dry whey and compositional mixtures to improve the nutritional properties and quality of sauces have been' experimentally proven. An important indicator of the structural and mechanical characteristics of sauces is shear stress. The content of mineral substances in the developed sauces increased: potassium - 1.25–4.3 times, calcium - 3.3–6.4 times, magnesium - 1.7–2.7 times, phosphorus - 1.2–2.9 times, iron - 1.6–8.5 times compared to the control. Analysis of the vitamin composition of the developed sauces revealed an increase in the content of vitamins. When studying the storage periods of the developed sauces, the number of mesophilic aerobic and facultative anaerobic microorganisms after storage (t = 4°C, 24 h) is 1.86–2.07•102, which is 6–9% less compared to the control. No mold fungi and yeasts were detected in the control and experimental samples.
Keywords: sauces; dairy raw materials; whey; emulsion systems; composite mixtures